New records of fleas (Siphonaptera: Ctenophthalmidae: Rhopalopsyllidae and Stephanocircidae) from Argentinean Patagonia, with remarks on the morphology of Agastopsylla boxi and Tiarapsylla argentina - Sánchez, Juliana Patricia (2014)
A high diversity of fleas parasitizing sigmodontine rodents has been mentioned for Patagonia. Several of these fleas have been described having their type localities in the region, including several endemic taxa. For many species, however, the original descriptions are brief and there are no new morphological contributions. In the present study we report 8 species of fleas (Ctenophthalmidae, Rhopalopsyllidae and Stephanocircidae) parasitizing sigmodontine rodents from Argentinean Patagonia. Nineteen new parasitehost associations are reported and all studied fleas extend their known geographic range. Among them, Tiarapsylla argentina is mentioned for the first time for Patagonia; Craneopsylla minerva, Sphinctopsylla ares, Polygenis (P.) platensis and Polygenis (P.) rimatus are registered for the first time for Chubut, and Agastopsylla boxi, Ectinorus (E.) ixanus and Ectinorus (E.) hapalus for Santa Cruz, extending the southernmost limit of their geographical distribution. Also, for A. boxi and T. argentina we describe the morphology of the aedeagus, so far unknown. Results extend the morphological information of fleas and contribute to the knowledge of Patagonian biodiversity.